Kontribusi Minat Baca terhadap Pengetahuan Siswa pada Mata Pelajaran Pendidikan Sejarah Islam (PAI) - Ghofir, Jamal; Setyono, Darwan (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2021)
Departing from the idea that reading interest has implications for the learning outcomes obtained by students. The initial provision in understanding learning material is the students reading comprehension ability. The aims of this research were to explain students' reading interest, and their knowledge achievement, and to find out the contribution of reading interest to the students' achievement of Islamic History Education subjects. This study employed an ex-post-facto quantitative approach. The subjects of this study were grade 9A students of SMP Negeri 2 Kerek, Tuban Regency. The data collection technique used was questionnaire and test. The data collected were analyzed by using the Simple Linear Regression data analysis technique. The results showed that reading interest had 46.90% a contribution to learning achievement of Islamic History Education. Meanwhile, the remaining 53.10% was affected by other factors. Furthermore, the significance test showed that the F value (26.47) was higher than the F table (4.17) at alpha (α) 5%. Thus, it explicitly concluded that students' reading interest has a significant contribution to the learning achievement of Islamic History Education subjects.